1997
DOI: 10.1063/1.366255
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of photoluminescence spectra in InAs/GaAs quantum dot superlattices with large thicknesses

Abstract: In this report, we investigate the thermal relaxation of the photoluminescence (PL) in InAs/GaAs quantum dot superlattices with large thicknesses that have two to more than three times the critical thickness for spontaneous island formation. It is found that the linewidth first decreases and then increases with increasing temperature. In addition to thermionic emission, we suggest that carrier repopulation among quantum dots plays an important role in the PL quenching. The temperature dependence of PL peak ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 14 publications
4
37
0
1
Order By: Relevance
“…The InAs QD PL intensity quenching is usually attributed to thermal escape of carriers from the QDs to the wetting layer (WL) or to the GaAs barrier with following recombination via non-radiative (NR) centers [4,5]. In DWELL structures the introduction of surrounding QWs changes the height of potential barriers for exciton thermal escape from QDs and can increase the density of NR centers.…”
Section: Introductionmentioning
confidence: 99%
“…The InAs QD PL intensity quenching is usually attributed to thermal escape of carriers from the QDs to the wetting layer (WL) or to the GaAs barrier with following recombination via non-radiative (NR) centers [4,5]. In DWELL structures the introduction of surrounding QWs changes the height of potential barriers for exciton thermal escape from QDs and can increase the density of NR centers.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the formula (6), that in high quality QD structures (#2, #3 and #4) with low concentrations of the NR1 and NR2 centres the PL intensity I(T) is linearly dependent on excitation power (or generation rates, G InGaAs , G GaAs ), as it is demonstrated in Fig.5. In low quality QD structures (#1 and #5) photo-generated excitons recombine partially via NR1 and NR2 centres and W (T) changes Sublineary versus power (Fig.5).…”
Section: Discussion Of Pl Integrated Intensity Dependences Versus Temmentioning
confidence: 85%
“…PL intensity decay in InAs QDs as a rule attributed to thermal escape of carriers from QDs into the wetting layer or into the GaAs barrier [5][6][7][8], as well as to thermally activated capture of excitons by nonradiative defects in the GaAs barrier or at the GaAs/InAs interface [5,9,10]. The unusual variations of emission energy and the full width at half maximum (FWHM) of PL bands in the InAs/GaAs self-assembled QDs have been investigated earlier as well [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size and hence emis− sion wavelength can be tuned by changing the growth con− ditions [7]. It has been shown that an increase in the InAs monolayer coverage leads to larger dots [8]. But increasing the monolayer coverage beyond 3 ML leads to other prob− lems such as coalescing of islands causing large non−unifor− mities in dot size [9].…”
Section: Introductionmentioning
confidence: 99%